VD_FINDINFO HC / 2020 / 936 vom 20. Januar 2021 - VD Tribunal cantonal (2021)
COURTAGE, NOUVEAU MOYEN DE FAIT, CONSTATATION DES FAITS | 412 al. 1 CO, 413 al. 1 CO, 229 CPC (CH), 310 CPC (CH), 311 CPC (CH)